Breast Carcinoma Masquerading as Granulomatous Mastitis on Fine Needle Aspiration Cytology lessons to learn! - Haque, Anwar Ul; Munir, Abdaal; Farooq, Hajra (International Journal of Pathology, 2018)
Chronic granulomatous mastitis is not an uncommon entity. It mimics breast carcinoma on physical, gross &microscopic examinations; both on histopathological and fine needle aspiration cytology. At other times invasiveductal carcinoma may suggest granulomatous mastitis. A case is presented here where ductal carcinoma wasmisinterpreted as granulomatous mastitis on fine needle aspiration cytology smears in a 48 yr old woman whopresented with large painful lump in her left breast. The mass was subsequently excised and thehistopathological examination revealed infiltrating ductal carcinoma. Reexamination of the cytology smears didshow some atypical cells commensurate with the ductal carcinoma. We here discuss various reasons and factorsresponsible for over and under interpretation of cytological atypia.